Lobby Activities and their Evolution in the European Union Context - Nicoleta Vasilcovschi; Stefan Ilie Oanta (CES Working Papers, 2014)
Beginning with the 20th century, lobby activities started to be developed and today the influence of the lobbying is used by nearly every group that has an important place at the international level. In this paper we describe the evolution of the concept of lobby at the international level and how this activity can influence European decision-makers. We consider that every citizen has the right to know how public decisions are designed, which interests are behind the allocation of resources, in which manner are expenses organized at central level and which are the techniques of influence. In this paper we explain how lobby activities help to analyse and design the decisions that affect the general interest.
Keywords: D72; 330; lobby; influence; decisions; partnership; EU lobby Romania